2020
DOI: 10.3390/ijms21113790
|View full text |Cite
|
Sign up to set email alerts
|

The Proliferation and Differentiation of Adipose-Derived Stem Cells in Neovascularization and Angiogenesis

Abstract: Neovascularization and angiogenesis are vital processes in the repair of damaged tissue, creating new blood vessel networks and increasing oxygen and nutrient supply for regeneration. The importance of Adipose-derived Mesenchymal Stem Cells (ASCs) contained in the adipose tissue surrounding blood vessel networks to these processes remains unknown and the exact mechanisms responsible for directing adipogenic cell fate remain to be discovered. As adipose tissue contains a heterogenous population of partially dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 174 publications
(229 reference statements)
1
66
0
Order By: Relevance
“…In contrast, dysregulated adipogenesis by ROS was demonstrated by increased proliferation of adipose-derived stem cells (ASCs) and preadipocyte differentiation [105,106], followed by a reduction of NOX4 content [107,108]. Moreover, hypoxia induces increased ASCs expression of vascular endothelial growth factor (VEGF), which in turn stimulates adipocyte proliferation [109]. Noteworthy, non-coordinated adipogenesis and angiogenesis may result in the impairment of recruitment and differentiation of ASCs, contributing to adipocyte hypertrophy [110].…”
Section: Obesity-induced At Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…In contrast, dysregulated adipogenesis by ROS was demonstrated by increased proliferation of adipose-derived stem cells (ASCs) and preadipocyte differentiation [105,106], followed by a reduction of NOX4 content [107,108]. Moreover, hypoxia induces increased ASCs expression of vascular endothelial growth factor (VEGF), which in turn stimulates adipocyte proliferation [109]. Noteworthy, non-coordinated adipogenesis and angiogenesis may result in the impairment of recruitment and differentiation of ASCs, contributing to adipocyte hypertrophy [110].…”
Section: Obesity-induced At Dysfunction and Oxidative Stressmentioning
confidence: 99%
“…In addition, tissue-derived stem cells have a degree of plasticity, depending on their type. This manifests in the differentiation phenotypic potential that goes beyond the cell phenotype of their original tissue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic neovascularization is characterized by proliferation and migration of abnormal cells [ 19 , 20 ]. In this study, we showed that in vivo, PSF ameliorated RNV and corrected aberrant VEGF expression in an OIR mouse model and reduced IRNV in Vldlr − / − mice.…”
Section: Discussionmentioning
confidence: 99%